Efeitos da dieta contendo disseleneto de difenila sobre respostas comportamentais, bioquímicas e moleculares em um modelo de hiperglicemia em peixe-zebra - Santos, Matheus Mülling dos (2018)
Studies have been demonstrating an increasing number of secondary complications caused by diabetes. Among them are neuropsychiatric diseases such as anxiety and depression. In addition, oxidative stress is known to play a key role in this metabolic disorder. Thus, compounds that have antioxidant activity have been considered as possible therapeutic agents in hyperglycemia models. In this context, we highlight diphenyl diselenide (DD), an organocalcogen with several pharmacological activities, including antioxidant and anxiolytic. In the present work, using zebrafish as a model organism, we investigated the effects of diet containing DD on behavioral, biochemical and molecular parameters in a model of hyperglycemia. Initially, in order to evaluate a possible toxicity of the compound, the fish were supplemented for 74 days with food containing 3 different concentrations of the compound (1, 2 and 3 mg / kg). After the 74 days, mortality rate analyzes as well as locomotor and anxiety-like behavior parameters (through the "light-dark" test and the "novel tank") did not show any alteration caused by supplementation. Therefore, we used the concentration of 3mg / kg in the hyperglycemia model. The animals were supplemented with diphenyl diselenide for 60 days. Then, they were exposed for 14 days to a solution of 111 mM glucose, remaining with the supplementation in that period. After that, blood glucose measurements, behavioral tests as well as biochemical and molecular analyzes were performed on the animals' brains. The glycemia of the animals exposed to glucose was increased around 3.5 times and supplementation with DD was able to partially reduce this increase. Through the "light-dark" test and the "novel tank" test, an increase in the anxiety-like behavior of animals exposed to glucose was observed. However, this effect was not observed in animals supplemented with DD. In order to understand possible mechanisms involved in the hypoglycemic effect as well as in the neuroprotection caused by DD, biochemical and molecular assays were performed in the fish’s brain. DD supplementation was able to prevent glucose-induced decrease in insulin receptor expression (Insra1, Insra2, Insrb1, Insrb2) in addition to increasing the expression of glucose transporter 3 (GLUT3). In the oxidative stress parameters, the diet containing DD partially prevented the decrease of the SOD enzyme activity caused by exposure to glucose and had an effect per se increasing the activity of the GPx and GST enzymes and the NPSH levels. In addition, DD supplementation was able to prevent the decrease caused by exposure to glucose in the expression of GPx3A and the transcription factor Nrf2. Finally, we evaluated lipid oxidation parameters (through the measurement of thiobarbituric acid reactive substances (TBARS)) and protein oxidation (through the levels of carbonylated preoteins (CP)). The results showed that both parameters were significantly increased by exposure to glucose and that the diet containing DD was effective in preventing this increase. The results of this work highlight the promising role of DD, in addition to showing for the first time possible mechanisms related to its hypoglycemic and neuroprotective effect.